Effects of tomato treatments with commercial formulations of entomopathogenic fungi on the pest Tuta absoluta and the predator Macrolophus pygmaeus - Sara Scovero; Silvia T. Moraglio; Luciana Tavella (Biological Control)
Tuta absoluta is a devasting pest causing severe yield losses in most tomato-growing areas. Macrolophus pygmaeus is a generalist predator released in tomato crop to control T. absoluta. Entomopathogenic fungi are also used on tomato against other pests, but they can play a role in controlling T. absoluta. Therefore, the effects of two commercial products Naturalis® and Mycotal®, based on the entomopathogenic fungi Beauveria bassiana and Akanthomyces muscarius, respectively, on T. absoluta and M. pygmaeus were assessed. In no-choice tests on leaflets, mortality was significantly higher on fungus-treated leaflets for 1st–2nd instar T. absoluta larvae, and not for 3rd–4th instar larvae and for both younger and older M. pygmaeus nymphs. Similarly, in no-choice tests on plants, development rate was significantly lower only for T. absoluta on plants treated with Mycotal®. In two-choice tests, both pest and predator did not show any preference between fungus-treated and untreated plants. Following the laboratory results, Mycotal® was applied also in plastic tunnel cultivation of tomato under field conditions. The number of T. absoluta larvae was significantly lower on plants treated with Mycotal® than on untreated plants, while the presence of M. pygmaeus was not affected by the treatment. Therefore, the use of fungal products together with the predator appears to be a promising strategy for the control of T. absoluta on tomato crop.